2011
DOI: 10.1029/2011ja016463
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic storms over the last solar cycle: A superposed epoch analysis

Abstract: [1] Presented here is a discussion of the results of a superposed epoch analysis of geomagnetic storms over the last solar cycle. Storms, identified by means of their characteristic SYM-H evolution, are separated by size into weak (−150 < SYM-H ≤ −80) nT, moderate (−300 < SYM-H ≤ −150) nT, and intense (SYM-H ≤ −300) nT categories. Where possible, the corresponding solar wind (SW) onset mechanisms were located by means of 1 min ACE OMNI data. Intense storms were observed to be driven solely by coronal mass ejec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
7

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 65 publications
(125 citation statements)
references
References 31 publications
7
111
7
Order By: Relevance
“…For example, Wang et al [2003] found that a southward field component Bz ≤ −3 nT with a duration of Δt ≥ 1 h results in moderate magnetic storms (Dst min ≤ −50 nT) and threshold values of Bz ≤ −6 nT with a duration of Δt ≥ 2 h result in strong magnetic storms (Dst min ≤ −100 nT), and these results differ somewhat from the results of previous papers by Russell et al [1974], Gonzalez and Tsurutani [1987], and Gonzalez et al [1994]. The papers mentioned above analyzed the duration of the southward IMF Bz component which is enough to generate magnetic storms, but the duration of the main phase was studied less intensively and it was shown that the duration of the main phase may be from 2 h to 1 day [see, e.g., Yokoyama and Kamide, 1997;Vieira et al, 2004;Vichare et al, 2005;Gonzalez and Echer, 2005;Yermolaev et al, 2007aYermolaev et al, , 2007bHutchinson et al, 2011;Nikolaeva et al, 2012, and Though it is well known that the dynamics of magnetic storms depends on the type of interplanetary drivers (see, e.g., papers by Borovsky and Denton [2006], Yermolaev et al [2010Yermolaev et al [ , 2012a, Guo et al [2011], Liemohn and Katus [2012], Nikolaeva et al [2013], Cramer et al [2013], and references therein), the majority of previous works have not made a selection by types of solar wind streams which generated the storms. In other works, the selection was either performed only for a limited type of solar wind or for a complex of types.…”
Section: Introductioncontrasting
confidence: 55%
See 4 more Smart Citations
“…For example, Wang et al [2003] found that a southward field component Bz ≤ −3 nT with a duration of Δt ≥ 1 h results in moderate magnetic storms (Dst min ≤ −50 nT) and threshold values of Bz ≤ −6 nT with a duration of Δt ≥ 2 h result in strong magnetic storms (Dst min ≤ −100 nT), and these results differ somewhat from the results of previous papers by Russell et al [1974], Gonzalez and Tsurutani [1987], and Gonzalez et al [1994]. The papers mentioned above analyzed the duration of the southward IMF Bz component which is enough to generate magnetic storms, but the duration of the main phase was studied less intensively and it was shown that the duration of the main phase may be from 2 h to 1 day [see, e.g., Yokoyama and Kamide, 1997;Vieira et al, 2004;Vichare et al, 2005;Gonzalez and Echer, 2005;Yermolaev et al, 2007aYermolaev et al, , 2007bHutchinson et al, 2011;Nikolaeva et al, 2012, and Though it is well known that the dynamics of magnetic storms depends on the type of interplanetary drivers (see, e.g., papers by Borovsky and Denton [2006], Yermolaev et al [2010Yermolaev et al [ , 2012a, Guo et al [2011], Liemohn and Katus [2012], Nikolaeva et al [2013], Cramer et al [2013], and references therein), the majority of previous works have not made a selection by types of solar wind streams which generated the storms. In other works, the selection was either performed only for a limited type of solar wind or for a complex of types.…”
Section: Introductioncontrasting
confidence: 55%
“…In the case of selecting by type of driver, our results show a small (within the statistical dispersion) peak in Figure 2 at Dst min in the range from −100 to −125 nT only for MC-induced storms (red line), while for the combined "ICME" = MC + Ejecta + Sheath type (similar to the type used in the work by Hutchinson et al [2011] and shown in Figure 2 by a black line), no maximum is observed.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations